2021
DOI: 10.1039/d1ra07821f
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antimicrobial treatment by a clay-based drug nanocarrier conjugated to a guanidine-rich cell penetrating peptide

Abstract: A novel anti-infection therapeutic nano-bioconjugate based on magnetized halloysite nanotubes and a CPP is presented. High levels of bactericidal effects have been obtained with the designed nanocargo in comparison with the individual drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 82 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Hence, it would be of high importance to highlight the advantages of the presented lvx@HNT/Au-CPP nano-cargo via true comparisons. Recently, a similar system was reported by Khodabakhshi and Baghersad, 22 which a guanidine-rich cell-penetrating peptide was considered for the conjugation onto the halloysite surfaces. As the first and foremost challenge, it be noticed that the total yield of the peptide synthesis process is quite low because of steric hindrance by the structure of the arginine amino acid.…”
Section: Comparisonsmentioning
confidence: 93%
See 3 more Smart Citations
“…Hence, it would be of high importance to highlight the advantages of the presented lvx@HNT/Au-CPP nano-cargo via true comparisons. Recently, a similar system was reported by Khodabakhshi and Baghersad, 22 which a guanidine-rich cell-penetrating peptide was considered for the conjugation onto the halloysite surfaces. As the first and foremost challenge, it be noticed that the total yield of the peptide synthesis process is quite low because of steric hindrance by the structure of the arginine amino acid.…”
Section: Comparisonsmentioning
confidence: 93%
“…For instance, Khodabakhshi and Baghersad used a magnetized system based on the HNTs for the delivery of vancomycin to the bacterial strains. 22 There, it was revealed that great co-localization was obtained for the HNTs and targeted bacteria cells, which resulted in an acceptable cell death ratio. Also, we previously experimented with heat-sensitivity of the HNTs that was exploited for the controlled release of taxotere (a cytotoxic agent) in the ovarian cancer cells.…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…[Zn–Al–NO 3 − ]–LDH encapsulated with biodegradable alginate beads for enhanced nitrogen fertilization, 23 composites of norfloxacin-intercalated Mg–Al LDH with carboxymethyl cellulose, cross-linked by citric acid for biomedical applications, 24 carboxymethyl cellulose-based nanocomposite hydrogel beads with Cu–Al LDH for bacterial infection treatment 18 and several other layered nanocomposites are reported to have shown controlled release property. 25–28 …”
Section: Introductionmentioning
confidence: 99%